2017
DOI: 10.7717/peerj.3536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freshwater mussels on the vertical distribution of anaerobic ammonia oxidizers and other nitrogen-transforming microorganisms in upper Mississippi river sediment

Abstract: Targeted qPCR and non-targeted amplicon sequencing of 16S rRNA genes within sediment layers identified the anaerobic ammonium oxidation (anammox) niche and characterized microbial community changes attributable to freshwater mussels. Anammox bacteria were normally distributed (Shapiro-Wilk normality test, W-statistic =0.954, p = 0.773) between 1 and 15 cm depth and were increased by a factor of 2.2 (p < 0.001) at 3 cm below the water-sediment interface when mussels were present. Amplicon sequencing of sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 148 publications
(209 reference statements)
4
24
0
Order By: Relevance
“…That genome harbored the metabolic potential for some fermentative pathways, hydrogen production or consumption and dissimilatory sulfate reduction. Interestingly, a recent amplicon sequencing survey of river sediments impacted by freshwater mussels discovered the co-occurrence of anammox bacteria, nitrate-and nitritedependent methanotrophs as well as Thermodesulfovibriolike sequences (Black et al, 2017). Their survey did not target sulfide-dependent denitrifiers, but proteobacteria were abundantly present and could potentially be involved in nitrate-dependent sulfide oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…That genome harbored the metabolic potential for some fermentative pathways, hydrogen production or consumption and dissimilatory sulfate reduction. Interestingly, a recent amplicon sequencing survey of river sediments impacted by freshwater mussels discovered the co-occurrence of anammox bacteria, nitrate-and nitritedependent methanotrophs as well as Thermodesulfovibriolike sequences (Black et al, 2017). Their survey did not target sulfide-dependent denitrifiers, but proteobacteria were abundantly present and could potentially be involved in nitrate-dependent sulfide oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Mussels are known ecosystem engineers that can substantially modify their habitats through biological processes such as sediment filtration and biodeposition of fecal matters (Bril et al 2014). The presence of mussels has been reported to cause to a 4-fold decrease in the relative abundance of Plantomycetes in a freshwater system in Mississippi, USA (Black et al 2017). Manuscript to be reviewed growth promoting and inhibiting effects to its host and other algal species, respectively (Bowman 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The most distinct nitrification genes were most closely related to NOB Nitrospira and comammox Nitrospira. It is not surprising that Nitrospira species dominated the nitrification biomarkers due to their metabolic diversity (Koch et al, 2015;Lücker et al, 2010), domination within freshwater sediments (Altmann, Stief, Amann, de Beer, & Schramm, 2003), increased abundance in sediments with mussels (Black et al, 2017;Zheng, Tang, Zhang, Qin, & Wang, 2017), and greater abundance from invertebrate bioturbation activities (Shen et al, 2017). Finding amoA biomarkers from comammox Nitrospira clades suggests that the presence of mussels may enhance the genetic potential for complete nitrification.…”
Section: Nitrification Biomarkers In Sediments With Musselsmentioning
confidence: 99%
“…In a previous study, we showed that sediment underlying a native freshwater mussel assemblage harbored microbial communities with lower species richness and evenness as compared to mussel-free sediment (Black, Chimenti, & Just, 2017). Additionally, mussels had a distinct and significant effect on the vertical distribution of multiple N-cycling microorganisms, including NO − 2 oxidizing bacteria (NOB) in the genus Nitrospira, aerobic NH 3 oxidizing bacteria (AOB) in family Nitrosomonadaceae, and anammox bacteria from candidate genus Brocadia.…”
mentioning
confidence: 98%